Gulf of Mexico oil blowout increases risks to globally threatened species - Campagna, Claudio (2011)
Fourteen marine species in the Gulf of Mexico are protected by the US Endangered Species Act, the Marine Mammal Protection Act, and the Migratory Bird Treaty Act. As the British Petroleum oil spill recovery and remediation proceed, species internationally recognized as having an elevated risk of extinction should also receive priority for protection and restoration efforts, whether or not they have specific legal protection. Forty additional marine species-unprotected by any federal laws-occur in the Gulf and are listed as threatened on the International Union for Conservation of Nature's (IUCN) Red List. The Red List assessment process scientifically evaluates species' global status and is therefore a key mechanism for transboundary impact assessments and for coordinating international conservation action. Environmental impact assessments conducted for future offshore oil and gas development should incorporate available data on globally threatened species, including species on the IUCN Red List. This consideration is particularly important because US Natural Resource Damage Assessments may not account for injury to highly migratory, globally threatened species. © 2011 by American Institute of Biological Sciences. All rights reserved.